Stakeholder expectations, inter-organizational coordination and procurement practices among humanitarian organizations - Mutebi, Henry; Aryatwijuka, Wilbroad; Rukundo, Aloysious; Twongyirwe, Ronald; Tumwebembeire, Naster; Tugiramasiko, Miriam (Journal of Business and Socio-economic Development, 2023)
Purpose: This paper aims to examine the interconnectedness between stakeholder expectations (SE), interorganizational coordination (IOC) and procurement practices within humanitarian organizations (HOs) based in Uganda. Design/methodology/approach: Employing a quantitative cross-sectional design, data were gathered from 43 HOs and analyzed using SmartPLS 4.0.8.3. Variance-based structural equation models (VB-SEMs) were employed to examine both direct and indirect effects. Findings: The findings show a significantly positive relationship between SE, IOC and procurement practices. Additionally, the mediating role of IOC in the relationship between SE and procurement practices is evident. Research limitations/implications: While this study offers insights into procurement practices in HOs, the use of a quantitative approach might limit capturing dynamic changes over time. Future research could benefit from a nuanced approach involving interviews and longitudinal studies to uncover incremental changes. Practical implications: During relief management, HOs need to understand their SE through information sharing and capacity building. This understanding can aid in selecting procurement practices that align with SE and ensure the delivery of relief. Originality/value: Leveraging stakeholder theory, this research contributes to the understanding of how SE and IOC influence the adoption of procurement practices in HOs during
Keywords: Stakeholder expectations; Inter-organizational coordination; Procurement practices